Direct and size‐dependent effects of climate on flowering performance in alpine and lowland herbaceous species. (6th March 2013) - Meineri, Eric; Skarpaas, Olav; Spindelböck, Joachim; Bargmann, Tessa; Vandvik, Vigdis; Prober, Suzanne
Abstract Questions Effects of climate on flowering performance are often investigated independently of plant size. We ask how temperature and precipitation impact flowering probability and flower production: via direct effects, size‐dependent indirect effects, changes in minimum size for flowering and/or changes in reproductive investment. Location Twelve calcareous grasslands in western Norway (4°50′–8°45′ E, 60°20′–61°50′ N). Methods The investigations were carried out at the rear temperature edge of alpine plants and at the leading temperature edge of lowland plants to capture the variety of climate responses occurring in different parts of species climate niches within our study landscape. The study was conducted within a natural 'climatic grid' consisting of temperature gradients replicated along a precipitation gradient. In each study site, we sampled populations of two alpine (Viola biflora, Veronica alpina) and two lowland (Viola palustris, Veronica officinalis) species. The relative importance of each effect was assessed under a 2 °C increase in mean summer temperature and a 10% increase in annual precipitation. Results Flowering was climate‐ and size‐dependent in all species except Viola palustris. Both direct climate effects and climate‐driven variation in reproductive investment were detected for the three other species. Indirect climate effects were detected for Veronica officinalis, and climate‐driven variation in minimum size for flowering in Viola biflora. Climatic responses were not consistent within or between distributional types (alpine vs lowland) or genera. A temperature increase of 2 °C was predicted to increase flower production by 22% for Veronica alpina and by 74% for Veronica officinalis. A precipitation increase of 10% had a limited impact on Viola biflora flowering probability (0.08% increase) and increased Veronica officinalis flower production by 1.7%. Conclusions Our study shows that climate affects flowering performance both directly and through size dependence. Understanding such size‐dependent responses to climate is important for our understanding of how climate change will affect flowering performance and recruitment in plant populations.